Application of Digital Terrain Model to volcanology - V. Achilli; R. Monticelli; M. Marsella; M. Fabris; P. Baldi (Annals of Geophysics, 2006)
Three-dimensional reconstruction of the ground surface (Digital Terrain Model, DTM), derived by airborne GPS photogrammetric surveys, is a powerful tool for implementing morphological analysis in remote areas. High accurate 3D models, with submeter elevation accuracy, can be obtained by images acquired at photo scales between 1:5000-1:20000. Multitemporal DTMs acquired periodically over volcanic area allow the monitoring of areas interested by crustal deformations and the evaluation of mass balance when large instability phenomena or lava flows have occurred. The work described the results obtained from the analysis of photogrammetric data collected over the Vulcano Island from 1971 to 2001. The data, processed by means of the Digital Photogrammetry Workstation DPW 770, provided DTM with accuracy ranging between few centimeters to few decimeters depending on the geometric image resolution, terrain configuration and quality of photographs.